New Trends of Sugarcane Cultivation Systems Toward Sugar Production on the Free Market: A Review - Andi Amran Sulaiman; Muhammad Arsyad; Achmad Amiruddin; Temesgen Tilahun Teshome; B. Nishanta (AGRIVITA, Journal of Agricultural Science, 2023)
Sugar is one of the staple food commodities that has an important role in the Indonesian economy. The high demand for domestic sugar has resulted in the inability of sugar factories to meet the demand for sugar consumption because domestic sugar production is still low. This is due to decreased land area and productivity, low sugar yield rates, and low factory efficiency. This paper describes the improvement of sugarcane cultivation to the process of making sugar to support national consumption. The article uses a systematic review method on the latest sugarcane research and reports the conditions directly on the plantation. The results show that the existing sugarcane supply is still less than the factory's demand, so the factory worked inefficiently. Even though the factory has new machines and technology to produce good quality sugar with a capacity of 4,600 TCD, companies can take a coaching approach to the surrounding community to carry out sugarcane cultivation and provide financial support to the surrounding community. Based on the reality of low production and factory efficiency, the government needs to support the sugarcane cultivation system through farming production systems, improving factory machine capacity and labor for sugarcane estate in the global market era.